2021
DOI: 10.1017/s095457942100047x
|View full text |Cite
|
Sign up to set email alerts
|

Behaviors in kindergarten are associated with trajectories of long-term welfare receipt: A 30-year population-based study

Abstract: This study examines the link between behavior in kindergarten and adult-life welfare receipt. Teacher-rated behavioral assessments were obtained for inattention, hyperactivity, aggression–opposition, anxiety, and prosociality when children (n=2960) were aged 5–6 years and linked to their tax return records from age 18–35 years. We used group-based based trajectory modeling to identify distinct trajectories of welfare receipt and multinomial logistic regression models to examine the association between behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 56 publications
0
5
1
Order By: Relevance
“…The same pathways may also play a role in the link between aggression-opposition and future earnings, although such a link has not always been found. Indeed, the total effect of aggression-opposition was not significant in the Vergunst, Tremblay, Nagin, Algan, Beasley, Park, Galera, et al (2019) study that used the same innercity low-income sample as the present study, whereas it was significant (for males only) in a population-based study of long-term welfare receipt (Vergunst et al, 2021). How might these diverging results be explained?…”
Section: Aggression-oppositioncontrasting
confidence: 60%
“…The same pathways may also play a role in the link between aggression-opposition and future earnings, although such a link has not always been found. Indeed, the total effect of aggression-opposition was not significant in the Vergunst, Tremblay, Nagin, Algan, Beasley, Park, Galera, et al (2019) study that used the same innercity low-income sample as the present study, whereas it was significant (for males only) in a population-based study of long-term welfare receipt (Vergunst et al, 2021). How might these diverging results be explained?…”
Section: Aggression-oppositioncontrasting
confidence: 60%
“…Our results build on a large body of literature linking childhood high externalizing symptoms and high internalizing symptoms to adverse social and economic outcomes across the life course. [6][7][8][46][47][48] Compared with the no/low symptom profile, participants in the high internalizing profile earned substantially less than participants in the high externalizing profile ($5904 vs $8473), even after adjusting for sex differences in earnings, which may be attributable to the higher burden of major depressive disorder in this population. For children in the high externalizing profile, estimated lost earnings across their working lives amounted to more than $140 515, while for children in the high externalizing profile the difference was more than $201 657.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical subjects with anxiety disorder, salivary oxytocin levels were negatively correlated with anxiety symptoms, suggesting a role of oxytocin in regulating anxiety (45). In kindergarteners, Wu and Su (46) found that oxytocin levels were significantly and positively associated with prosocial behaviors in children from 3 to 5 years old, in which childhood prosocial behaviors were found to be significantly associated with a lower risk of having socioeconomical difficulties in adulthood, a common adversity, in a recent population-based study (47). In addition, a longitudinal study demonstrated the association between oxytocin receptor genes polymorphism and childhood adversities starting from kindergarten years (48).…”
Section: Oxytocinmentioning
confidence: 95%